PENGARUH PENYULUHAN TENTANG KPSP TERHADAP PENGETAHUAN GURU DI PAUD TAMAN BELIA SEMARANG - Dita Wasthu Prasida; Maftuchah -; Dewi Mayangsari (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2015)
The quality of a children's development should be increased since the children are in their Toddlers time for their developments determine the further developments, so the slightest deviation must be detected and handled properly as not to reduce the quality of human resources in the future later. One instrument of stimulation, detection and early intervention of growth and development for children at age of 3 to 72 months drawn up by the health Office in coordination with Indonesian Pediatric Association (IDAI) is a Pre-screening questionnaire development (). The purpose of this study was to analyze the effect of counseling on KPSP toward the knowledge of teachers at PAUD (early childhood education) Taman Belia Candi Semarang. The design of this study is quantitative comparative using a quasi-experimental methods (quasi experi-mental) with pre-post test, a sample of 22 early childhood teachers using total sampling. Bivariate analysis was done by using paired t-test after completing the data normality test using Shapiro-Wilk. The Average knowledge before the extension was 9.77 and deviation standard 1998. While the average knowledge after counseling was 16 with 2,045 SD, visible differences between the mean value of measurements before and after counseling. Results of statistical test t-paired with p value 0.000 <0.05, then there was a significant difference in knowledge between before and after counseling about KPSP. The conclusion is KPSP counseling was capable of improving knowledge effectively. And for Candilama Public Health Center and the ECD are expected to improve cooperation in efforts to monitor the children’s development.Keywords: Development, Pre-Screening Questionnaire Development (KPSP)